Identification of special competences for Master degree in dentistry: draft. - Ya. Kulbashna; O. O. Gudaryan; V. V. Nikonov; N. G. Idashkina (Medičnì Perspektivi, 2016)
The article deals with the problem of identifying specific competencies of Master in dentistry. The results of the analysis of domestic and foreign scientific literature, legal documents regulating the implementation of competence-based approach in higher medical education is presented, international experience in the modernization of higher education, including medical, on the basis of changes in the educational paradigm on competence approach is studied. In the process of identifying set of special competences of Master of dentistry, the main ideas of the existing professional Standards in Dentistry were used. A worked out set of special competences reflects peculiarities of the profession in accordance with the algorithm, aimed to help dental patient in a vicious circle from disease prevention to rehabilitation after diseases, the latter includes legal, methodical, social and managerial aspects of the professional activities of a dentist.